A wearable textile antenna for wireless power transfer by magnetic resonance. Issue 8 (April 2018) - Heo, Eunah; Choi, Keun-Yeong; Kim, Jooyong; Park, Jong-Hu; Lee, Hojin
The paper presents a wearable textile antenna embroidered on a fabric for wireless power transfer systems. A planar spiral coil was generated with the conductive thread on a cotton substrate, and was connected to a rectifier circuit fabricated on flexible polyethylene terephthalate film to constitute a bendable receiver by the magnetic resonance. At a resonance frequency of 6.78 MHz, the proposed system could achieve −5.51 dB transfer efficiency and 12.75 mW power transmission at a distance of 15 cm. It was also demonstrated that the resonance frequency and transmitted power of the proposed system could be maintained as the same even when the system was bent conformingly to the surface curvature of the human body model for a bending radius up to 50 mm or larger.